2005
DOI: 10.1089/cbr.2005.20.77
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Modeling of Gamma Cameras for I-131 Imaging in Targeted Radiotherapy

Abstract: The modeling of two gamma cameras (DST-XLi and Millennium VG Hawk-Eye) has been performed with two Monte Carlo codes (MCNP and Gate). Results obtained with the two Monte Carlo codes agree well with experimental results. As already indicated by several authors, septal penetration and scattered photons in the collimator have a major impact on I-131 scintigraphic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 13 publications
1
30
0
Order By: Relevance
“…Camera geometry and features: The GATE simulator allows any gamma camera simulation, provided that an accurate description of the system is given. 6,7 Model-specific gamma camera information is stored in the 'Camera' database (see figure 1). …”
Section: Simulation Of Spect Imagesmentioning
confidence: 99%
“…Camera geometry and features: The GATE simulator allows any gamma camera simulation, provided that an accurate description of the system is given. 6,7 Model-specific gamma camera information is stored in the 'Camera' database (see figure 1). …”
Section: Simulation Of Spect Imagesmentioning
confidence: 99%
“…Autret et al (2005) showed the impact of the scattered and septal penetration photons in the projection images by means of Monte Carlo simulations.…”
Section: System Matrix Pmentioning
confidence: 99%
“…Currently, this is often done using scintigraphic wholebody planar images. For a limited number of agents (mostly 131 I), radiation produced by the isotope can be used for imaging, but the images obtained with single photon emission computed tomography (SPECT) scanners are often of poor quality for a variety of reasons [2,3].…”
Section: Introductionmentioning
confidence: 99%